Dual-functional biomimetic periosteum incorporating engineered small extracellular vesicles for treating critical bone defect with soft tissue fenestration via TGF-beta1/SMAD pathway - Zhengchuan Zhang; Jiaqi Shen; Ruogu Xu; Yang Yang; Xiaolin Yu; Dongsheng Yu; Feilong Deng (Materials Today Bio)
Critical bone defect with soft tissue fenestration poses a significant therapeutic challenge without the premise of barrier periosteum in situ for the relatively independent repair spaces of soft tissue and bone. Inspired by the regenerative functions of mesenchymal stem cells (MSCs)-derived small extracellular vesicles (sEVs) and the guided properties of in situ-generated periosteum, here we report the therapeutic benefits of dual-functional biomimetic periosteum (DBP) incorporating engineered sEVs for treating critical bone defect with soft tissue fenestration. We started our experiment with the construction of engineered sEVs via porous titanium-preconditioned MSCs-derived sEVs (Ti-sEVs). COL1A1 and MMP1 were enriched in Ti-sEVs with enhanced uptake efficiency of fibroblasts and bone marrow-derived MSCs for scarless soft tissue and bone repair abilities via TGF-beta1/SMAD pathway in vitro. DPB was constructed via the chemically crosslinking and lyophilized treatment of a xenogenic acellular dermal matrix. Incorporation and in vivo delivery of Ti-sEVs were successfully achieved via the controlled-release DPB with the characteristics of a loose surface facing the bone defect and a dense surface facing the soft tissue fenestration. DBP incorporating Ti-sEVs promoted the repair of the surrounding native periosteum in situ via the critical skull defect with skin fenestration models in rats. Bone repair with scarless soft tissue was achieved by enhanced angiogenesis and limited osteoclastic activity. Collectively, this dual-functional system could synergistically achieve critical bone defect regeneration with scarless soft tissue repair via TGF-beta1/SMAD pathway with the sustained release of Ti-sEVs, providing a promising strategy of engineered sEVs for preferable tissue regeneration.